Effect of feed flow rate and addition of maltodextrin towards spray drying of pineapple: article - Mazelan, Nurul Afidah; Abd. Hashib, Syafiza (2017)
Sample of pineapple powder was produced using the LabPlant SD-Basic Spray Dryer under two different conditions. Slurry of flesh, pulp and skin of pineapple were added with 15%, 20% and 25% concentration of maltodextrin (MD) before feeding to the spray dryer at fixed temperature 130°C using 3rpm, 4rpm and 5rpm speed pump. The powder were then analysed for moisture content. The physicochemical properties such as total soluble solids (TSS) and Titratable Acidity (TA) were also determined. The highest yield of powder produced at 3rpm which is in the range of 0.45 L/hr to 0.60 L/hr feed flow rate with 25% addition of maltodextrin. Result showed that lower feed flow rate and increment of maltodextrin content decresing the moisture content of pineapple powder. TA were significantly decrease as the concentration of maltodextrin increase. TSS in pineapple juice significantly increase when turn into powder but was not affected by the increment of maltodextrin and feed flow rate